Bakuchiol kills Staphylococcus aureus persisters and potentiates colistin activity against Acinetobacter baumannii persisters - Suh, Kayeong; Lee, Yeju; Baek, Seongeun; Kim, Jin; Seo, Jinbeom; Yang, Yung-Hun; Kim, Jae-Seok; Lee, Wonsik; Seo, Eun Kyoung; Kim, Wooseong (Frontiers in Pharmacology, 2025)
Infections associated with bacterial persisters are challenging to cure because they can evade antibiotics and regrow, often resulting in relapse. Current antibiotics are not optimized to target persisters, highlighting the urgent need for new therapeutics. Here, we report that bakuchiol, a plant-derived natural product, exhibits anti-persister and adjuvant properties. Bakuchiol eradicates persisters formed by the gram-positive bacterium Staphylococcus aureus at 8 μg/mL and, in combination with 1 μg/mL colistin, completely eliminates persisters formed by the gram-negative bacterium Acinetobacter baumannii. Mechanistic analyses revealed that bakuchiol selectively disrupted bacterial membrane phospholipids while sparing mammalian membranes and exhibited low cytotoxicity. In Acinetobacter baumannii persisters, bakuchiol likely damages phospholipid patches in the outer membrane, causing nominal lethality but facilitating membrane permeabilization. This activity synergizes with colistin, which targets the lipooligosaccharide layer, resulting in the mutual reinforcement of their bactericidal effects. These findings highlight the potential of dual glycolipid–phospholipid targeting as a strategy to combat gram-negative persisters and highlight natural products as valuable sources for anti-persister therapeutics with membrane selectivity.